Pelatihan Budidaya Anggrek Bagi Siswa SMK Negeri 1 Rasau Jaya Kubu Raya Kalimantan Barat - Dwi Gusmalawati; Rafdinal Rafdinal; Irwan Lovadi; Siti Khotimah; Firman Saputra (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Orchids are planting whose existence in nature is decreasing. Cultivation to preserve orchids needs to be done. However, orchid cultivation requires special knowledge and skills in order for the plants to thrive. This training was conducted to increase knowledge and skills about orchid cultivation for students of SMK Negeri 1 Rasau Jaya Kubu Raya. The method of implementing this activity includes preparation (Activity plan), implementation (Delivery of material and practice of orchid cultivation) and evaluation (Filling out questionnaires). This activity was carried out at Talita Garden Rasau Jaya III Rasau Jaya Kubu Raya which was attended by 16 participants. The material and practice of orchid cultivation were delivered directly by the resource person. Based on the evaluation through the questionnaire sheet, this training was able to increase the knowledge and skills of participants about orchid cultivation from 81.25% not knowing to 40.00% knowing and 60.00% very knowing. This training was very useful (68.75%) and inspiring (100%). Based on the knowledge and skills of orchid cultivation that have been obtained, participants hope to practice at school and at home.